Population Dynamics and Policies in Europe: Analysis of Population Resilience at the Subnational and National Levels - Vytenis Juozas Deimantas; A. Ebru Şanlıtürk; Leo Azzollini; Selin Köksal (Population Research and Policy Review, 2024)
While previous research has focused on the relationship between population dynamics and policies in Europe, there has been scarce attention on dynamics at the NUTS-3 level. By looking at the population measures at subnational regions in Europe we seek to identify average population dynamics since year 2000. We group subnational regions by countries in terms of average population dynamics and assess the connection between population policies in 1996 and average population dynamics in 2000–2017 using data from World Population Policy database, the UN Population Division, the World Bank's World Development Indicators and Eurostat. We find that urban areas and Western and Northern Europe exhibit population growth whilst rural areas and Central, Eastern, and Southern Europe have more depopulating regions. Our analyses also suggest a negative association between fertility policies and population growth.
Keywords: 300; Population dynamics; Fertility; Migration; Policy; Europe